2015
DOI: 10.4067/s0718-07052015000200004
|View full text |Cite
|
Sign up to set email alerts
|

Pensamiento de los profesores de historia acerca de la ciudadanía y la inclusión de las movilizaciones estudiantiles en su enseñanza

Abstract: estudiantiles en su enseñanza* History teachers' thinking on citizenship and the inclusion of the student mobilizations into their teaching Pensamento dos professores de história a respeito da cidadania e a inclusão das mobilizações estudiantiles em seu ensino

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There are interesting similarities between our results and those of other investigations in Chile. Like the teachers that participated in the study undertaken by Cavieres and Muñoz (2015), the teachers interviewed in our study also expressed their desire to participate more actively and directly in the democratic process. They also expressed their appreciation of the recent student protest movements, which placed these teachers mainly within a participatory conception of citizenship.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are interesting similarities between our results and those of other investigations in Chile. Like the teachers that participated in the study undertaken by Cavieres and Muñoz (2015), the teachers interviewed in our study also expressed their desire to participate more actively and directly in the democratic process. They also expressed their appreciation of the recent student protest movements, which placed these teachers mainly within a participatory conception of citizenship.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…More recently, the work of Cavieres Fernández and Muñoz Reyes has indicated that Chilean history teachers share a collective rather than individualistic conception of citizenship, together with a desire (that is not always fulfilled) to see active participation (Cavieres Fernández and Muñoz Reyes 2015). The same study also found that teachers related the student protest movement to the exercise of active citizenship (Cavieres Fernández and Muñoz Reyes 2015), which represents an important contextual conditioning factor.…”
Section: History Teachers' Conceptions Of Citizenshipmentioning
confidence: 94%
“…Prior studies have explored teachers' views and definitions of citizenship (Alviar‐Martin, 2011; Leenders et al, 2008), teacher priorities regarding political or citizenship education (Reichert & Torney‐Purta, 2019) or the relation between their set of beliefs and pedagogical practices (Gainous & Martens, 2016; Knowles, 2018; Sampermans et al, 2021). In Chile, a number of studies have focused on the way in which citizenship is both defined and understood in the curriculum and by different actors in education (Cavieres Fernández & Muñoz Reyes, 2015; Jara Ibarra et al, 2019; Salinas et al, 2016), but the analysis of teachers' views on different forms of political participation (clearly noticeable in the socio‐political context) has not been approached.…”
Section: Concepts and Literature Review On Political Contexts Curricu...mentioning
confidence: 99%